1999
DOI: 10.1006/jevp.1999.0129
|View full text |Cite
|
Sign up to set email alerts
|

Values as Predictors of Environmental Attitudes: Evidence for Consistency Across 14 Countries

Abstract: A multinational study is reported on the relationship between values and attitudes. Environmental attitudes were measured using the revised New Environmental Paradigm (NEP: Dunlap et al., 1992) and Thompson and Barton's (1994) ecocentrism-anthropocentrism scales. Other measures included gender, SES, religion, and Schwartz's (1994) universal values scale. Survey data were obtained from college students in 14 countries. A sample of 2160 participants was obtained through university contacts in each country. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
142
2
13

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 772 publications
(207 citation statements)
references
References 18 publications
14
142
2
13
Order By: Relevance
“…Research has also shown that ecocentrism correlates negatively with the conservation values. By contrast, research has revealed that anthropocentrism is negatively correlated with the self-transcendence values, positively correlated with the self-enhancement values, and positively correlated with the conservation values (Nordlund & Garvill, 2002;Schultz & Zelezny, 1999).…”
Section: Ecocentric and Anthropocentric Environmental Philosophiesmentioning
confidence: 87%
See 1 more Smart Citation
“…Research has also shown that ecocentrism correlates negatively with the conservation values. By contrast, research has revealed that anthropocentrism is negatively correlated with the self-transcendence values, positively correlated with the self-enhancement values, and positively correlated with the conservation values (Nordlund & Garvill, 2002;Schultz & Zelezny, 1999).…”
Section: Ecocentric and Anthropocentric Environmental Philosophiesmentioning
confidence: 87%
“…Other studies have found substantial positive correlations at .20 or more (Bjerke & Kaltenborn, 1999;Kaltenborn & Bjerke, 2002;Schultz & Zelezny, 1999). Some studies have found that women have more positive attitudes towards ecocentrism than men (Casey & Scott, 2006;Karpiak & Baril, 2008).…”
Section: Ecocentric and Anthropocentric Environmental Philosophiesmentioning
confidence: 97%
“…Schwartz ([6], p. 12) defines universalism based on the motivational goal behind its manifestation: "understanding, appreciation, tolerance, and protection for the welfare of all people and for nature." Schultz and Zelezny [13] The literature suggests that security is related to anthropocentric attitudes [13]. Thus, H 4 : Individuals with high levels of security engage in less ECCB.…”
Section: Self-transcendence Valuesmentioning
confidence: 95%
“…The demand segments were identified by cluster analysis (Ward Method, Euclidean distance) of the questionnaires from both surveys (the scale of the rate of participation on partial recreational activities). The estimated credibility loss ratio was 50% as in Real et al (2000). The questionnaires from the model segments (i.e., students) were selected from the identified clusters.…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…The differences in the average appeal among the types of areas were investigated by one-way ANOVA with Tukey unequal N HSD post-hoc tests (Quinn and Keough 2002).…”
Section: Data Processing and Analysismentioning
confidence: 99%